Explicitly racialised and extraordinarily over-represented: Black immigrant men in 25 years of news reports on HIV non-disclosure criminal cases in Canada. Issue 6 (1st June 2021) - Mykhalovskiy, Eric; Sanders, Chris; Hastings, Colin; Bisaillon, Laura
Abstract: This paper explores newspaper coverage of HIV non-disclosure criminal cases in Canada in which defendants are Black immigrant men living with HIV. We base our analysis on a corpus of 1680 English-language Canadian newspaper articles written between 1989 and 2015. For the first time ever, we present quantitative evidence of the dramatic overrepresentation of Black men in such coverage. We also provide an analysis of the racialised regime of representation found in this material. We emphasise how 'writing in criminal justice time' operates as a first-order objectification within which are embedded strategies that link constructions of moral blameworthiness with representations of racialised difference. The result is a type of popular racial profiling in which HIV non-disclosure is treated as a crime of Black men who are represented as dangerous, hypersexual foreigners who threaten the health and safety of the public and, more broadly, the imagined Canadian nation.